2020
DOI: 10.1177/0267659120954381
|View full text |Cite
|
Sign up to set email alerts
|

Changes of biventricular function after CABG surgery: does cardioplegia type matter?

Abstract: Aim: we choose to evaluate, whether type of cardioplegia is an important predictor to determine biventricular function changes after CABG. Methods: 81 patients who underwent CABG surgery and matched inclusion criteria were enrolled in this study. The exclusion criteria were acute MI within 30 days, impaired systolic left ventricle function (LVEF ⩽35%), atrial fibrillation.TTE was performed for all patients and echocardiographic parameters of biventricular geometry and function were assessed before CABG surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Furthermore the study of Ordienė, Unikas [32] who studied the changes of biventricular function after CABG surgery and found that the reduction was seen right after the surgery had a tendency to improve within the follow-up period (6 months) [32]. Similarly, the study of John, Thomas [33] found signi cant increase in the RV function post CABG over the next 2 months after surgery [33].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore the study of Ordienė, Unikas [32] who studied the changes of biventricular function after CABG surgery and found that the reduction was seen right after the surgery had a tendency to improve within the follow-up period (6 months) [32]. Similarly, the study of John, Thomas [33] found signi cant increase in the RV function post CABG over the next 2 months after surgery [33].…”
Section: Discussionmentioning
confidence: 97%